Peripartum Cardiomyopathy in Preterm Pregnant Women during the Covid 19 Pandemic - Putri Handayani (Faculty of Medicine, Universitas Andalas, 2021)
Peripartum cardiomyopathy (PPCM) is a life-threatening disease with left ventricular (LV) dysfunction towards the end of pregnancy or in the months following delivery in women previously had no heart disease. Symptoms of heart failure (HF) are the main clinical manifestations of PPCM. Many pregnant women near the end of pregnancy experience shortness of breath, fatigue, swelling of the legs, which are symptoms identical to normal effects found in pregnancy. These symptoms are almost similar to early HF, so they often go unnoticed by medical personnel. Objective: We reported a case of PPCM that occurred during preterm pregnancy. Case: 29 years old woman, 33-34 weeks pregnant with a history of severe preeclampsia. The patient complained worsening shortness of breath for the last 5 days, but suspected that the symptom was just a normal process of growing pregnancy. In echocardiography examination found that the patient had LV dysfunction with low ejection fraction (EF) of 30%. The patient was diagnosed with PPCM in preterm pregnancy. Conclusion: Based on this case report, early identification of PPCM is a good predictor of outcome, because early treatment is given.Keywords: Peripartum cardiomyopathy; heart failure; pregnancy